Genetic polymorphisms of CYP2C8 in the Czech Republic - Pechandova, Kristina; Buzkova, Helena; Matouskova, Olga; Perlik, Frantisek; Slanar, Ondrej (Genetic testing and molecular biomarkers, 2012)
AIM: CYP2C8 represents 7% of the hepatic cytochrome system and metabolizes around 5% of drugs in phase I processes. It also plays a significant role in metabolism of endogenous compounds. More than 20 single-nucleotide polymorphisms (SNPs) have been noted, mainly in exons 3, 5, and 8. The most studied SNPs may lead to decreased enzyme activity and may have impact on drug metabolism. Variant alleles are called CYP2C8*2 (I269F), CYP2C8*3 (R139K, K399R), and CYP2C8*4(I264M). Our aim was to investigate the frequency of major functional SNPs among the Czech population. MATERIAL AND METHODS: DNA was isolated from whole blood of 161 healthy, young, and unrelated subjects (94 men and 67 women, aged from 23 to 28 years). The genotypes of polymorphic positions CYP2C8*2, CYP2C8*3 (G416A, A1196G), and CYP2C8*4 were determined by polymerase chain reaction-restriction fragment length polymorphism. RESULTS AND CONCLUSION: Observed allele frequencies were 10.9%, 5.9%, and 0.3% for the alleles CYP2C8*3, CYP2C8*4, and CYP2C8*2, respectively. Both CYP2C8*3 (G416A, A1196G) alleles have been found in complete linkage disequilibrium. The allele distribution complies well with Hardy-Weinberg equilibrium. Allele frequencies of functionally important CYP2C8 variants in the Czech population are similar to that of other Caucasian populations.
Keywords: alely; Polymorphism, Single Nucleotide; exony; Humans; aromatické hydroxylasy; Polymorphism, Restriction Fragment Length; jednonukleotidový polymorfismus; Female; dospělí; frekvence genu; Aryl Hydrocarbon Hydroxylases; Alleles; Exons; lidé; Adult; ženské pohlaví; Male; Czech Republic; Gene Frequency; polymorfismus délky restrikčních fragmentů; Česká republika; mužské pohlaví